USING E-LEARNING IN TEACHING OF THE MATRICES - Matoušová, Ivana; Kulička, Jiří (International Association of Technology, Education and Development (IATED), 2019)
Students of Faculty of Transport Engineering, University of Pardubice, usually have never met matrices before enter the university. Therefore the calculation with matrices is sometimes very difficult for these students. E-learning could help them to study matrices. With the development of information and communication technologies, the term e-learning is currently inextricably linked with education. E-learning uses information and communication technologies for education. The aim of this study is to show the specific use of e-learning for the introduction of the matrices during mathematics lessons, publication of the study material, homework, testing and evaluation. For this purpose, exercises and tests were developed using the system WebWork. The paper describes the using of the system STAG for the publication of the study material and the assessment. All presented exercises and tests were practically used in the teaching of mathematics at Faculty of Transport Engineering, University of Pardubice. This study introduces experiences of users (lectures and students) with the systems WebWork and STAG.
Využití e-learningu při výuce matic
Keywords: e-learning; e-learning; matrix; teaching methods; matice; metody výuky